The Responsibility of the State in the Prevention and Suppression of Genocide: An Analysis from the Perspective of Constitutional Law - Tomy Michael (Indonesian Red Crescent Humanitarian Journal, 2026)
The state must demonstrate commitment to addressing genocide. From a state science perspective, a state is an entity capable of addressing and fighting for what its people desire. A state's capabilities extend beyond simply attempting to influence activities within its borders. One example is social responsibility, which is the duty of companies to formulate policies, make decisions, and take actions that benefit society. Corporate social responsibility is crucial in crisis situations such as genocide. This research prioritizes a statutory regulatory approach. A statutory regulatory approach is part of normative research. A statutory regulatory approach provides a snapshot of the research being conducted within the statutory regulations. This will yield concrete answers and rational recommendations. In this section, it is necessary to emphasize, both conceptually and normatively, that the state plays a fundamental and irreplaceable role in the prevention, reduction, and handling of genocide in order to achieve legal justice. Genocide cannot be understood merely as an individual criminal act or as an isolated episode of violence; rather, it constitutes an extraordinary crime that is structurally and systemically intertwined with state power, either through acts of commission or omission. Therefore, genocide is conceptually inseparable from the state, as it generally occurs within the context of power relations, public policy, and national legal and political structures. As the holder of the highest authority within the legal and governmental system, the state bears both international and domestic legal obligations to prevent the occurrence of genocide. These obligations are explicitly articulated in the Convention on the Prevention and Punishment of the Crime of Genocide of 1948, which positions the state not only as a subject required to punish perpetrators of genocide, but also as the primary actor responsible for undertaking preventive measures. Consequently, a state’s failure to prevent genocide may be regarded as a violation of its international legal obligations, with direct implications for the erosion of legal justice and the protection of human rights.